Terapi Farmakologi Epidural Analgesia pada Persalinan Normal dengan Kestabilan Tanda Vital Bayi Baru Lahir - Justina Purwarini; Sandro Yuan Sykenario (Jurnal Keperawatan Silampari, 2022)
This study aims to determine the relationship between pharmacological therapy of epidural analgesia in normal delivery and the stability of newborns' vital signs at X Hospital Jakarta. The study used secondary data, electronic medical records, patient registration books and used quantitative methods with a cross-sectional approach. The results showed a significant relationship between temperature with p-value = 0.000 OR 5.179 (95% CI 2.684-9.992), respiratory rate with p-value = 0.027 OR 4.377 (95% CI 1.055-18.160) with and without epidural analgesia. There is no significant relationship between the first minute APGAR scores, p-value = 0.486 using the chi-square test and fifth p-value = 1,000 and pulse p-value = 0.621 using the Fishers exact test. In conclusion, epidural analgesia is safe for both mother and baby with proper monitoring. Keywords: Epidural Analgesia, Breathing Frequency, Pulse, Normal Delivery, APGAR